School Emotional Environment and Academic Supports as Predictors of Students2019; Success in Public Secondary Schools in Rivers State of Nigeria (Global Journal of Human-Social Science, 2020)
The study investigated school emotional environment and academic supports as predictors of students success in public secondary schools in Rivers State of Nigeria Two 2 research questions and 2 hypotheses guided the study The design of the study was correlational with the population as the 268 public secondary schools in the state from which 468 principals teachers and students were selected as sample using the purposive and simple random sampling techniques The study had 2 validated instruments the School Emotional Environment and Academic Supports Scale SEEASS and Students Success Index SSI designed by the researchers with reliability indices of 0 85 and 0 81 respectively Linear regression while z-test associated with linear regression was used in testing the hypotheses at 0 05 level of significance The results of the study show that school emotional environment and academic supports predict student success by 11 1 and 47 0 respectively The findings also establish that there is no significant prediction of school emotional environment on student success and a significant prediction of academic supports on students success
Keywords: school emotional environment; academic supports; predictors; students success